L2 learner age from a contextualised perspective - Mihaljević Djigunović, Jelena (Array, 2014)
In this qualitative study the author focuses on age effects on young learners’ L2 development by comparing the L2 learning processes of six young learners in an instructed setting: three who had started learning English as L2 at age 6/7 and three who had started at age 9/10. Both earlier and later young beginners were followed for three years (during their second, third and fourth year of learning English). The participants’ L2 development was measured through their oral output elicited by a two-part speaking task administered each year. Results of the analyses are interpreted taking into account each learners’ individual characteristics (learning ability, attitudes and motivation, self-concept) and the characteristics of the context in which they were learning their L2 (attitudes of school staff and parents to early L2 learning, home support, in-class and out-of-class exposure to L2, socio-economic status). The findings show that earlier and later young beginners follow different trajectories in their L2 learning, which reflects different interactions which age enters into with the other variables.